2020
DOI: 10.1111/spc3.12533
|View full text |Cite
|
Sign up to set email alerts
|

The role of individual differences in understanding and enhancing intergroup contact

Abstract: In a world characterized by divisive rhetoric, heightened xenophobia, and other forms of prejudice, it is increasingly important to find effective ways of promoting functional intergroup relations. Research on the relationship between intergroup contact and individual differences substantially contributes to achieving this goal. We review research considering the role played by individual differences in moderating the relationship between contact and prejudice and predicting contact, but also as an outcome of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 115 publications
(161 reference statements)
2
52
2
Order By: Relevance
“…Decades of research revealed the effectiveness of contact for the improvement of intergroup relations, even in the absence of the optimal contact conditions (Pettigrew & Tropp, 2006). Also, in contrast to Allport's (1954) initial concerns, intergroup contact was shown to be effective (and in some cases, its effects are even stronger) among individuals more intolerant of the outgroup (Turner, Hodson, & Dhont, 2020). Research has also demonstrated that the effects of contact generalize from known outgroup members to the outgroup as a whole, especially when group membership is salient during contact (Brown & Hewstone, 2005).…”
Section: Intergroup Contact and The Secondary Transfer Effectmentioning
confidence: 99%
“…Decades of research revealed the effectiveness of contact for the improvement of intergroup relations, even in the absence of the optimal contact conditions (Pettigrew & Tropp, 2006). Also, in contrast to Allport's (1954) initial concerns, intergroup contact was shown to be effective (and in some cases, its effects are even stronger) among individuals more intolerant of the outgroup (Turner, Hodson, & Dhont, 2020). Research has also demonstrated that the effects of contact generalize from known outgroup members to the outgroup as a whole, especially when group membership is salient during contact (Brown & Hewstone, 2005).…”
Section: Intergroup Contact and The Secondary Transfer Effectmentioning
confidence: 99%
“…A strong individual-difference predictor of prejudice is social dominance orientation (SDO): an orientation toward supporting group hierarchy and inequality (Altemeyer, 1998;Duckitt, 2005;Sidanius & Pratto, 1999 (Dhont & Van Hiel, 2009;see Turner et al, 2020), mediated by elevated empathy (Hodson, 2008) and trust (Hodson et al, 2015) and decreased threat (Dhont & Van Hiel, 2011;Hodson et al, 2009). Such patterns seem less tenable in the immediate wake of COVID-19; variability in these mediators will become restricted, and prejudiced-persons may be sensitive to PSYCHOLOGICAL SCIENCE IN THE WAKE OF COVID-19 22 negative contact (Turner et al, 2020). Therefore, contact's benefits on prejudice may become newly contested due to face-to-face intergroup contact reducing in frequency, with contact becoming less relevant to predicting bias, and/or contact thresholds becoming less reachable.…”
Section: Prejudicementioning
confidence: 99%
“…However, ethnographic and observational data have confirmed that even in diverse settings where opportunities for intergroup contact are high, individuals still predominantly interact with members of their ingroup (Dixon et al, 2005(Dixon et al, , 2020. Not only does intergroup avoidance impact research agendas, but low levels of intergroup contact stifle efforts to build welcoming societies through naturally occurring intergroup contact (Dixon et al, 2005;Paolini et al, 2018;Turner et al, 2020). By acknowledging these issues, researchers may rethink their use of intensive repeated research designs to directly promote intergroup contact.…”
Section: Methods For Understanding Daily Life: Intensive Longitudinalmentioning
confidence: 99%